¿Ciudadanos de color? - Alejandro E. Gómez (Centre de Recherches sur les Mondes Américains, 2007)
In the late 18th century appeared in France a group of enlightened philanthropists who promoted the suppression of African slave trade and the abolition of slavery. These aims persisted during the French Revolution, during which many of them also supported the cause of political equality for Free Coloureds. The ideological struggles that took place along that process between those who were in favor or against slavery, was strongly influenced by the situation in the French Antilles. There, the revolution had generated great expectations of freedom and equality among Slaves and Free Coloureds respectively. In consequence, a series of conflicts broke out affecting in different ways policymaking in the French metropolis concerning those racial sectors. This article studies from an Atlantic perspective the way those events interacted with that metropolitan ideological debate, pointing out the way the concept of Citizenship was adapted to be applied to multi-ethnic societies in the French Antilles.